Calcium has protective impact on cadmium-induced toxicity in lichens - Kováčik, Jozef; Dresler, Sławomir; Babula, Petr; Hladký, Juraj; Sowa, Ireneusz (Plant physiology and biochemistry, 2020)
Eventual protective action of calcium (Ca, 100 or 1000 μM) against cadmium (Cd, 10 or 100 μM) toxicity in common lichen Hypogymnia physodes after 24 h of exposure was studied. Total Cd reached 482 and 2801 μg/g DW in 10 and 100 μM Cd treatments while Ca content reached over 23 mg/g DW in 1000 μM Ca treatment. Ca suppressed Cd accumulation by 23 and 38% in total fraction and completely in absorbed fraction. Fluorescence microscopy of Cd and Ca ions revealed good correlation with quantitative data. Cd stimulated increase in ROS formation and lipid peroxidation as detected using fluorescent reagents and quantification of H2O2 while co-application of Ca suppressed these effects. Formation of nitric oxide was mainly affected by cadmium. Cd depleted amount of amino acids but proteins or phenols remained unaffected by Cd or Ca. On the contrary, sum of thiols, reduced glutathione and ascorbic acid were depleted by Cd but reversed mainly by higher Ca dose. Among organic acids, only Cd-induced depletion of citric acid content was reversed by Ca. Data indicate that ameliorative effect of Ca under Cd excess in lichens is comparable with effect in plants and metabolic responses in various life lineages are discussed.
Keywords: antioxidancia; Calcium; vápník; Lichens; Cadmium; lišejníky; peroxid vodíku; terčovkovité; Microscopy; oxid dusnatý; Reactive oxygen species; Antioxidants; Hydrogen Peroxide; Fungi; Nitric Oxide; Heavy metals; Parmeliaceae; kadmium